Variability of indicators of the width of the maxillary dental arches depending on the skull type - E. Yu. Efimova; A. I. Krayushkin; Y. V. Efimov (Сеченовский вестник, 2018)
Morphometric data on the linear parameters of the dental arches are informative, diagnostically signiﬁcant values and have a use in practical dentistry. Interpretation of indicators can be used to characterize physiological occlusion, as well as predicting the shape and size of dental arches in the treatment of patients with dentoalveolar anomalies. The morphometric parameters of the width of the maxillary dental arches with diﬀerent skull types were investigated. The work was performed on 187 skull preparations of mature persons of both sexes with physiological occlusion of teeth. The width of the dental arch was measured between canines, premolars and molars. As a result of the study, the minimum and maximum limits and the average statistical indices of the width of the dental arches at diﬀerent levels of measurement in mesocranial, brachicranial and dolichocranial skull types are determined depending on sex. A signiﬁcant diﬀerence in the average dental arches of the upper jaw in men and women in all craniotypes was observed only at the level of the ﬁrst premolars and only on the vestibular side of the arch.